1329 IMPROVING ADVANCED CARE PLANNING IN SEVERE FRAILTY. (16th January 2023) - Sawney, P; Rehman, H; Ali, S; Alicehajic-Becic, D; Clarke, E; Khan, K; Roughneen, K; Leigh, E
Abstract: Introduction: NICE guidance recommends that doctors need to identify patients who are approaching their final year of life, through the utilisation of tools such as the Clinical Frailty Score (CFS). The 'Getting it right first time' (GIRFT) document recommended that all local health systems identify older people in the last phase of life and offer them Advanced Care Planning (ACP). Wigan has a large population of frail patients who would benefit from ACP discussions. Aim: Initiate a strategy for identifying patients with severe frailty and establish a process for implementing ACP. Method: Retrospective discharge data was used to identify patients aged >65 years, with a CFS of >7, over an 8-week period. The cohort was examined to see if they had been recognised as a patient who would benefit from ACP, or if an aspect of ACP had been completed during their admission. In total, 19 patients were identified, of which 6 were included and 13 were excluded. Results: Initial data showed that we were poor at identifying and completing ACPs for patients with severe frailty. No advanced care planning decisions (0%) were taken during this period. Education (PDSA cycle 1) on ACPs for the ward doctors led to an improvement regarding ACP discussions. However, we were still poor at identifying severe frailty. Education (PSDA cycle 2) for nursing staff was undertaken, which highlighted inaccuracies with calculating CFS. Further PDSA cycles are to follow, including a geriatric frailty score assessment, introduction of Electronic Palliative Care Coordination Systems (EPACCS) and frailty posters and cards. Conclusion: Severe frailty is an end-of-life state and should trigger a healthcare professional to identify and sensitively discuss end of life needs and preferences. ACP should be disseminated to other healthcare professionals to allow them to act in accordance with the patient's wishes or best interests.